A relação entre ecclesía e koinonía: uma leitura eclesiológica do quarto evangelho a partir de João 15,1-8 - Morais, Pedro da Silva (2017)
The absence of the words ekklesía and koinonía in the sets of texts of the Fourth Gospel surprises the listener-reader. The author of the Gospel does not explicitly address the subject of ecclesiology, without concern for the constitution or organization of the community. Their concern seems to lie in the intimate relationship of communion/unity with believers, members of the Church, with Christ and with one another. The present research aims to address this question of the relationship between ekklesía and koinonía in an ecclesiological reading of the texts of the Fourth Gospel, in order to understand the intimate relationship between church and communion from the text 15:1-8 divided into two parts. In the first moment he will present an exegetical study of text 15:1-8 and then a biblical-theological study, deepening the nature of the Church in the image of the “vine and branches”, which highlights the union of those who “believe” with Jesus, A community that abides in him and lives the promise that he abides in them. This emphasis on the personal relationship of one who believes with Jesus does not suppress an authentically community reflection of the Gospel for our day and our ekklesíal reality